Impact of fear of crimes on public transport usage: A case study of Delhi - Dubey, Rabindra Nath (National Geographical Journal of India, 2022)
Delhi Transport Corporation (DTC and Delhi Metro-Rail System (DMRS) are two important public transport systems in Delhi. The DMRS has been attractive in respect to ridership but in 2015 it has shown a decrease in its ridership. It has also been found that ridership of the bus service, the most important public transport system for the poor in Delhi, has decreased over time whereas the numbers of private vehicles have recorded phenomenal increase resulting in traffic congestions and pollution problems in the city. The purpose of this study is to explore the role of the fear of crimes along with other reasons for decreasing trends in the usage of public transport in Delhi. The study is based on people opinion and perception for which 350 persons were interviewed with the structured questionnaire from ten transit places having varied socio-economic conditions. Fear of crimes within buses/coaches is considered an important reason for not using public transport in western countries but as per this study, the same is not true in the case of Delhi. Role of fear of crimes along with other factors was verified with the spearman's correlation coefficient. The weak negative correlation has been found between the preference to public bus services and the fear of crimes; the crowing; the unavailability. It indicates that along with these other factors are equally responsible for the choice of public transports in Delhi.